2020
DOI: 10.3390/jcm9010144
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Chuna Manipulative Therapy for Non-Acute Lower Back Pain: A Multi-Center, Pragmatic, Randomized Controlled Trial

Abstract: Current evidence on the effectiveness and safety of Chuna manipulative therapy (CMT) for managing non-acute lower back pain (LBP) is insufficient. We investigated the comparative effectiveness and safety of CMT, a Korean style of manipulation, plus usual care (UC) compared to UC alone for non-acute LBP. We conducted a parallel, two-armed, multi-centered, assessor blinded, pragmatic, randomized controlled trial at four major Korean medical hospitals. Overall, 194 patients were randomly allocated to either CMT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Where allowed, concomitant treatments were unrestricted in 30 trials (68% of applicable cases) and 6 trials permitted any concomitant treatment other than those akin or similar to the study interventions. Some trials excluded individual unrelated interventions, such as injections and surgery, 88 injections alone, 87 physiotherapy, 16 tricyclic antidepressants, 5 or pain medication (not further specified). 59 , 102 Only one drug trial made specific allowances for medications and dosages, including some of the same class as study interventions and opioids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where allowed, concomitant treatments were unrestricted in 30 trials (68% of applicable cases) and 6 trials permitted any concomitant treatment other than those akin or similar to the study interventions. Some trials excluded individual unrelated interventions, such as injections and surgery, 88 injections alone, 87 physiotherapy, 16 tricyclic antidepressants, 5 or pain medication (not further specified). 59 , 102 Only one drug trial made specific allowances for medications and dosages, including some of the same class as study interventions and opioids.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, common medications were a reason for noneligibility in 7 studies (12%). Once enrolled, patients were advised not to seek additional care outside the trial in 9 studies (16%) 19 , 23 , 35 , 49 , 88 , 93 , 102 , 111 , 127 ; the report was unclear on that point in 19 instances.…”
Section: Resultsmentioning
confidence: 99%
“…An NRS allowed a person to describe the intensity of his/her pain as a number usually ranging from 0 to 10, where "0" meant "no pain" and "10" meant pain as "bad as it could be," and the patient circled a number to represent the degree of pain. We regarded 0 as painless, 1 to 3 as mild pain, 4 to 6 as moderate pain, and 7 to 10 as severe pain [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…Chuna manual therapy for the treatment of musculoskeletal disorders has been covered by the South Korean national health insurance since April 2019. Subsequently, it became possible to examine the use of manual therapy for musculoskeletal disorders to determine its efficacy and cost-effectiveness ( 12 , 13 ). A recent study demonstrated that Chuna manual therapy (Chuna) was more effective in relieving pain and improving function and quality of life than usual care (i.e., Western medicine, such as physical therapy) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%